BDE-209 induces male reproductive toxicity via cell cycle arrest and apoptosis mediated by DNA damage response signaling pathways. (December 2019) - Li, Xiangyang; Zhu, Yupeng; Zhang, Chonghai; Liu, Jianhui; Zhou, Guiqing; Jing, Li; Shi, Zhixiong; Sun, Zhiwei; Zhou, Xianqing
Abstract: Decabromodiphenyl ether (BDE-209) is commonly used as a flame retardant, usually in products that were utilized in electronic equipment, plastics, furniture and textiles. To identify the impacts of BDE-209 on the male reproductive system and the underlying toxicological mechanisms, 40 male ICR mice were randomly divided into four groups, which were then exposed to BDE-209 at 0, 7.5, 25 and 75 mg kg −1 d −1 for four weeks, respectively. With regard to the in vitro study, GC-2spd cells were treated with BDE-209 at 0, 2, 8 and 32 μg mL −1 for 24 h, respectively. The results from the in vivo experiments showed that BDE-209 resulted in damage to the testis structure, led to cell apoptosis in testis and decreased sperm number and motility, while sperm malformation rates were significantly increased. Moreover, BDE-209 could induce oxidative stress with decreased testosterone levels, result in DNA damage and activate DNA damage response signaling pathways (ATM/Chk2, ATR/Chk1 and DNA-PKcs/XRCC4/DNA ligase Ⅳ). The data from the in vitro experiments showed that BDE-209 led to cytotoxicity by reducing cell viability and increasing LDH release as well. BDE-209 also induced DNA strand breaks, cell cycle arrest at G1 phase and elevated reactive oxygen species (ROS) level in GC-2 cells. These results suggested that BDE-209 could lead to male reproductive toxicity by inducing DNA damage and failure of DNA damage repair which resulted in cell cycle arrest and apoptosis of spermatogenic cell. The present study provided new evidence to elucidate the potential mechanism of male reproductive toxicity induced by BDE-209. Graphical abstract: Image 1 Highlights: BDE-209 induced DNA damage resulting from oxidative stress. BDE-209 activated DDR signaling pathways causing cell cycle arrest and apoptosis. BDE-209 decreased sperm quality and quantity due to cell apoptosis. BDE-209 caused cytotoxicity in GC-2 by ROS-induced DNA damage. Abstract : Main finding: BDE-209 induced reproductive toxicity due to DNA damage and failure of DNA repair which caused cell cycle arrest and apoptosis of spermatogenic cell.